C3d,g is present in normal human epidermal basement membrane - Basset-Seguin, N; Dersookian, M; Cehrs, K; Yancey, K B (The Journal of immunology (1950), 1988)
mAb as well as polyclonal anti-human C3d antibodies were found to specifically bind to the epidermal basement membrane zone of normal human adult and neonatal skin in a linear continuous pattern on direct immunofluorescence microscopy. No such binding was found in dermal microvascular basement membranes. Studies of normal adult human skin using a rat mAb specific for C3g revealed the same pattern of epidermal basement membrane staining. Control polyclonal antibodies directed against C3, C3c, C5, IgG, IgA, or IgM showed no evidence of epidermal basement membrane binding or in situ deposits of immune complexes in samples of normal human skin that were all positive for C3d and C3g. Pre-adsorption of monoclonal or polyclonal anti-human C3d with purified human C3d completely blocked these reagents' epidermal basement membrane reactivity. Anti-human C3d epidermal basement membrane binding was not diminished by pre-treatment of substrate with antibodies directed against C3, C3c, C5, laminin, fibronectin, or type IV collagen as well as bullous pemphigoid, KF-1, or epidermolysis bullosa acquisita Ag. Direct immunofluorescence microscopy studies on 1 M NaCl split human skin showed that C3d and C3g were found in the base of the cleavage plane created within the lamina lucida. By immunoelectron microscopy, C3d was found along the base of the lamina densa and in the sublamina densa region of normal human epidermal basement membrane. Although anti-human C3d epidermal basement membrane binding was not altered by treatment of 6 micron skin sections with buffers of varying pH and ionic concentration, binding was abolished by treating dermal portions of salt split skin with 0.1 M dithiothreitol in 8 M urea. Studies of a patient with congenital C3 deficiency revealed that there was no binding of anti-human C3d or anti-human C3g to this subject's epidermal basement membrane. Moreover, treatment of this patient's skin with aged human serum containing C3d,g or purified human C3 did not restore epidermal basement membrane anti-human C3d binding. These studies demonstrate that C3d,g or a closely related C3 fragment is present in the epidermal basement membrane zone of normal human skin.